2018
DOI: 10.1101/304808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4 alpha (HNF4α) Activation is Essential for Termination of Liver Regeneration

Abstract: Hepatocyte Nuclear Factor 4 alpha (HNF4α) is critical for hepatic differentiation. Recent studies have highlighted its role in inhibition of hepatocyte proliferation and tumor suppression.However, the role of HNF4α in liver regeneration is not known. We hypothesized that hepatocytes modulate HNF4α activity when navigating between differentiated and proliferative states during liver regeneration. Western blot analysis revealed a rapid decline in nuclear and cytoplasmic HNF4α protein levels accompanied with decr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
1
10
0
1
Order By: Relevance
“…Consistent with our regulon activity scores, HNF4A protein levels diminish rapidly after PHx, and this initial decrease followed by re-expression is needed for hepatocytes to timely enter and exit the cell cycle and to re-establish mature liver functions once regeneration is complete (Huck et al, 2019).…”
Section: Rewiring Of Gene Regulatory Network Activates Cell State Transitions During Regenerationsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with our regulon activity scores, HNF4A protein levels diminish rapidly after PHx, and this initial decrease followed by re-expression is needed for hepatocytes to timely enter and exit the cell cycle and to re-establish mature liver functions once regeneration is complete (Huck et al, 2019).…”
Section: Rewiring Of Gene Regulatory Network Activates Cell State Transitions During Regenerationsupporting
confidence: 85%
“…The function of hepatocyte nuclear factor 4A (HNF4A), a nuclear receptor, in hepatocyte differentiation is well established (Kyrmizi et al, 2006;Parviz et al, 2003) -as it directs the expression of gene programs involved in xenobiotic, carbohydrate, and fatty acid metabolism as well as in bile acid synthesis, blood coagulation, and ureagenesis (Hayhurst et al, 2001;Inoue et al, 2002b;2006a;2004;2006b;Nishikawa et al, 2015;Schrem et al, 2002). Previous studies have described HNF4A's anti-proliferative effects in hepatocytes (Bonzo et al, 2012;Hatziapostolou et al, 2011;Walesky et al, 2013), and more recently, it was found that HNF4A is indispensable for terminating regeneration after PHx (Huck et al, 2019).…”
Section: Rewiring Of Gene Regulatory Network Activates Cell State Transitions During Regenerationmentioning
confidence: 99%
“…Hepatocyte HNF4α deficiency has been linked to spontaneous hepatocyte proliferation as well as defective termination of LR (15,16). Therefore, we investigated HNF4α expression and activity in OGT-KO mice 28 days after PHX.…”
Section: Hnf4α Expression and Activity Declined In Ogt-ko Livers After Phxmentioning
confidence: 99%
“…A recent study reported that PP2Acα terminates LR in mice via the AKT/GSK3β/Cyclin D1 signaling pathway [6]. Ian Huck found that knockout of hepatocyte nuclear factor 4 alpha increased hepatocyte proliferation throughout LR and that HNF4a activation was crucial for the termination of liver regeneration in mice [7].…”
Section: Introductionmentioning
confidence: 99%